2021
DOI: 10.1111/bor.12530
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stratigraphical sequences at Cocina Cave (Spain) using rare earth elements geochemistry

Abstract: This study investigates the stratigraphical sequence of Cocina Cave (Spain) employing and testing for the first time the capability of rare earth elements as markers of human activities in caves. Located in Dos Aguas (Valencian Community, Spain), Cocina Cave is characterized by the presence of several Holocene archaeological deposits from the final Mesolithic to the present day and is a pivotal site for understanding the socio-ecological dynamics of the last hunter-gatherer inhabitants of the Iberian Peninsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Equally, our data obtained in Cocina Cave (Spain) [ 18 , 19 ] showed that REE geochemistry was controlled by carbonate and phosphate phases in an alkaline environment, while REE fractionation marked the difference between Mesolithic, Neolithic and Bronze Age layers.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Equally, our data obtained in Cocina Cave (Spain) [ 18 , 19 ] showed that REE geochemistry was controlled by carbonate and phosphate phases in an alkaline environment, while REE fractionation marked the difference between Mesolithic, Neolithic and Bronze Age layers.…”
Section: Introductionmentioning
confidence: 75%
“…Therefore, following the research aim, the digestion method consisted of aqua regia . Further details on acid digestions can be found in a previous work published by Gallello and colleagues [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…frontiersin.org proxies to reveal the source, genesis, and sedimentary environment (Jiang et al, 2019;Gallello et al, 2021;Romero et al, 2021;Zhang X et al, 2021;Deng et al, 2022a).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%